PENGARUH PERILAKU PEMIMPIN, KARAKTERISTIK TUGAS DAN HARAPAN BAWAHAN TERHADAP KEPUASAN ATAS KEPEMIMPINAN DI LINGKUNGAN DINAS PENDIDIKAN KABUPATEN DONGGALA SULAWESI - ASPINA ASPINA (Universitas Negeri Jakarta, 2010)
Subordinates’ satisfaction to the leadership in an organization is assumed to be affected by the leaders’ behavior, the task characteristics and their expectancies. The study reported here aimed to examine how the three variables actually affected the subordinates’ satisfaction to the leadership in the office of education of the Donggala Regency, Central Sulawesi, and also how they affected each other. The causal study was conducted in the form of a survey to the employees in the Donggala Regency in their capacities as subordinates. The sample consisted of 97 employees, randomly selected from the overall number of employees of 129. The data of each variable were collected separately with a questionnaire. A path technique was employed to analyze the data with the SPSS technique. Result show direct effects of the leaders’ behaviors and the characteristics of the tasks on the subordinates’ expectancies, direct effects of subordinates’ expectancies on their satisfaction to the leadership style, but indirect effects of the leaders’ behaviors and the task characteristics on the subordinates’ satisfaction to the leadership through their expectancies. These findings suggest that the variables of leaders’ behaviors’ task characteristics, and subordinates’ expectancies are important determinants of satisfaction to the leaderhips. Improvement in the satisfaction to the leadership style my be therefore be expected by improved behaviors of the leaders, characteristics of the tasks and the subordinates’ expectancies.